The digital transformation and business processes of the manufacturing companies - Trujillo Valdiviezo, Guido; Mejía Ayala, Desmond; Ríos Yovera, Verónica (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Innovation and technology are important for the economic development of companies, since, the greater the investment in technology and innovation, it will have the greater the possibility of improving its business processes, and this will lead to generating new resources, between economic and human, and thus guarantee its permanence in a highly competitive market. The study was cross-sectional and non-experimental in design, based on the information provided by the business managers. The research determined that digitized processes through digital transformation contribute to the development of the strengthening of the business sector.